In vitro hypoxia increases production of matrix metalloproteinases and tryptase in isolated rat lung mast cells - Maxová, Hana; Novotná, Jana; Vajner, Luděk; Tomášová, Helena; Vytášek, Richard; Vízek, Martin; Bačáková, Lucie; Valoušková, Věra; Eliášová, T; Herget, Jan (Physiological research, 2008)
haracterized by fibrotization and muscularization of the walls of peripheral pulmonary arteries. This vessel remodeling is accompanied by an increase in the amount of lung mast cells (LMC) and the presence of small collagen cleavage products in the vessel walls. We hypothesize that hypoxia activates LMC, which release matrix metalloproteinases (MMPs) cleaving collagen and starting increased turnover of connective tissue proteins. This study was designed to determine whether in vitro hypoxia stimulates production of MMPs in rat LMC and increases their collagenolytic activity. The LMC were separated on the Percoll gradient and then were divided into two groups and cultivated for 24 h in 21 % O2+ 5 % CO2 or in 10 % O2 + 5 % CO2. Presence of the rat interstitial tissue collagenase (MMP-13) in LMC was visualized by immunohistological staining and confirmed by Western blot analysis. Total MMPs activity and tryptase activity were measured in both cultivation media and cellular extracts. Exposure to hypoxia in vitro increased the amount of cells positively labeled by anti-MMP-13 antibody as well as activities of all measured enzymes. The results therefore support the concept that LMC are an important source of increased collagenolytic activity in chronic hypoxia.
Keywords: Animals; Lung; Mast Cells; krysa rodu Rattus; kultivované buňky; Matrix Metalloproteinase 13; Up-Regulation; matrixová metaloproteinasa 9; mužské pohlaví; matrixová metaloproteinasa 2; Financing, Organized; kolagen; Matrix Metalloproteinase 2; imunohistochemie; Matrix Metalloproteinase 9; Cell Hypoxia; Tryptases; Cell Separation; Rats; Matrix Metalloproteinases; kultivační média; Male; matrixová metaloproteinasa 13; matrixové metaloproteinasy; mastocyty; Culture Media; tryptasy; Immunohistochemistry; zvířata; financování organizované; Tryptase; plíce; Collagen; potkani Wistar; Cells, Cultured; western blotting; Hypoxia in vitro; separace buněk; Rats, Wistar; Remodeling of pulmonary vessels; upregulace; Rat lung mast cells; Blotting, Western; Tissue metalloproteinases; hypoxie buňky